Harmony of mysterious japanese poetry with the kazakh poetry - Орaзбек, М. С.; Тaлaспaевa, Ж. С. (Journal of Oriental Studies, 2017)
This article investigatedscientist and writer Zhanat Askerbekkyzy translation skills of Japanese poetry into Kazakh language. Comprehensively considered gentle lyricism and interest in the life of trees, flowers, birds in the natural world, and particularly depicting their relationship to human life inherent in the Japanese poets.